Exchange rate determination and adjustment - Bhandari, Jagdeep S. (New York, N.Y. : Praeger, 1982)
This book is a collection of studies on exchange rate determination and adjustment. Its model of analysis was based on general equilibrium nature, while its investigation is Dornbusch. It examines the hypothesis adapted and their implications for exchange rate volatility and dynamics.
Includes bibliographical references.
usc 24/05/18
Loans
Keywords: Foreign exchange; Foreign exchange--Mathematical models